Cistudinella inanis (Boheman, 1854), un registro nuevo de país para Paraguay (Coleoptera: Chrysomelidae: Cassidinae: Ischyrosonychini) - Bezark, Larry (2022)
This note reports Paraguay as a new country record for Cistudinella inanis (Boheman, 1854) based on one adult specimen, that is currently deposited in the Larry Bezark collection which eventually reside in the Bohart Museum of Entomology, University of California, Davis, USA.